An Area-Wide Real-Time Database for the Euro Area - Giannone, Domenico; Henry, Jérôme; Lalik, Magdalena; Modugno, Michele (The Review of Economics and Statistics, 2012)
This paper describes how we constructed a real-time database for the euro area. The database covers more than 200 series regularly published in the European Central Bank Monthly Bulletin, as made available to the Governing Council members for their first monthly meeting. We study the properties of the real-time data flow and data revisions in the euro area, also providing comparisons with the United States and Japan. We illustrate how revisions contribute to the uncertainty surrounding key macroeconomic ratios and the non-accelerating inflation rate of unemployment.